Apparatus and method for spin transfer torque switching of a magnetic layer having bulk uniaxial magnetic crystalline anisotropy

By forming a Heusler compound magnetic electrode on an amorphous substrate and deposition at room temperature using the Mn-nitride template layer, the thickness and switching current density limitations of existing MRAM devices when reducing size are solved, and high-quality, perpendicular magnetic oriented are achieved Ultra-thin film growth of the opposite sex supports scaling below 20nm.

CN110970551BActive Publication Date: 2025-01-07SAMSUNG ELECTRONICS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN201910318506.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-28
Filing Date
2019-04-19
Publication Date
2025-01-07
Estimated Expiration
2039-04-19

AI Technical Summary

Technical Problem

The existing magnetic random access memory (MRAM) devices encounter magnetic electrode thickness and switching current density limitations when reducing the size, resulting in the inability to effectively overcome thermal fluctuations, and the material interface anisotropy is insufficient, making it difficult to achieve less than 20nm Zoom.

Method used

Using Heusler compounds as magnetic electrode material, by forming ultra-thin films on amorphous or polycrystalline substrates, and using Mn-nitride as chemical template layer to deposit Heusler films at room temperature to avoid high-temperature thermal annealing, ensuring vertical alignment of magnetic moments and high-quality magnetic Academic nature.

Benefits of technology

It realizes the growth of high-quality, perpendicular magnetic anisotropy ultra-thin Heusler film under CMOS manufacturing conditions, enhances the switching performance of magnetic memory, reduces the switching current density, and supports the scaling of the MRAM device to a size below 20nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110970551B_ABST
    Figure CN110970551B_ABST
Patent Text Reader

Abstract

A device is disclosed. The device includes: a first magnetic layer having volume uniaxial magnetic crystallographic anisotropy, wherein a magnetic moment of the first magnetic layer is perpendicular to the first magnetic layer; and a tunnel barrier adjacent to the first magnetic layer, wherein the orientation of the magnetic moment of the first magnetic layer is reversed by a spin transfer torque caused by a current flowing between and through the first magnetic layer and the tunnel barrier.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims priority to U.S. Patent Application No. 16 / 146,728, filed on September 28, 2018, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0002] The present invention relates to the field of magnetic random access memory (MRAM), and more particularly to MRAM devices that rely on spin transfer torque. Background Art

[0003] Magnetic tunnel junctions (MTJs) form the fundamental memory cell of new non-volatile magnetic random access memories (MRAMs) that hold promise for high performance and endurance, and also have the potential to be scaled to extremely small sizes. A magnetic tunnel junction (MTJ) consists of a sandwich of two magnetic electrodes separated by an ultrathin insulating layer. One of these layers forms the memory or storage layer, the other forms a reference layer whose magnetic structure does not change during MRAM operation. The current tunneling between the reference electrode and the memory magnetic electrode is spin-polarized: the magnitude of the spin polarization is determined by a combination of the electronic properties of the magnetic electrodes and the "spin filtering" properties of the tunnel barrier.

[0004] In current MRAM, the magnetic state of the MTJ is changed by passing a current through the MTJ, regardless of whether the magnetization of the electrodes forming the memory layer is oriented parallel or antiparallel to the magnetization of the reference electrode. The current (which is inherently spin-polarized) transfers spin angular momentum, which, once a threshold current is exceeded, causes the direction of the magnetic moment of the magnetic memory electrode to switch. The transfer of this spin angular momentum applies a spin transfer torque (STT), and the magnetic memory electrode switched by this method is called STT-MRAM. When the magnetization of the electrode is oriented perpendicular to the layer, the magnitude of the switching current is reduced. The magnitude of this current is limited by the size of the transistor used to provide the write current. This means that the thickness of the switchable magnetic electrode (memory electrode) must be small enough so that it can be switched by the available current. Therefore, for about 1000emu / cm 3 To obtain a magnetization value of 0.0040 W, the electrodes must have a thickness of no more than about 1 nm.

[0005] The most promising materials currently being developed for MTJs for dense MRAM include ferromagnetic electrodes formed of an alloy of Co, Fe, and B, and tunnel barriers formed of MgO (e.g., U.S. Pat. No. 8,008,097). The ferromagnetic electrodes are made thin enough so that the magnetization of these electrodes is oriented perpendicular to these layers. The perpendicular magnetic anisotropy (PMA) of the Co-Fe-B layer is caused by the interface between these layers and the tunnel barrier and / or the bottom layer on which the Co-Fe-B layer is deposited. Therefore, these layers must be made thin enough so that the interface PMA overcomes the demagnetization energy caused by the magnetic volume and increases proportionally with the magnetic volume of the Co-Fe-B layer. In practice, this means that when the device size is reduced to less than about 20nm, the PMA is too weak to overcome thermal fluctuations because the thickness of the magnetic layer has to be less than the thickness required to maintain its perpendicular magnetic moment and less than the thickness required to switch the magnetic layer at a reasonable current density. To date, magnetic materials whose magnetic moments can be switched by STT in MRAM devices have interface anisotropy, shape anisotropy, or no anisotropy. Such materials do not allow MRAM devices to be scaled to sizes below about 20 nm. What is needed is a new material for ferromagnetic electrodes that exhibits a much greater PMA than that exhibited by Co-Fe-B, and preferably the PMA arises from the bulk or bulk phase of the electrode. One promising class of magnetic materials with this property is the Heusler compounds. Heusler alloys are materials with the chemical formula X 2 YZ or X'X"YZ compounds, wherein X and X' and X" and Y are transition metals or lanthanides (rare earth metals), and Z is selected from the main group metals. Heusler compounds have Cu 2 MnAl-type structure (defined in the Pearson Table), in which these elements are arranged on four interpenetrating face-centered cubic (fcc) lattices. Many compounds are known in this family (about 800) (T. Graf et al., Progress in Sol. State Chem. 39, 1 (2011)). Some of these compounds are ferromagnetic or ferrimagnetic due to magnetic moments at the X and / or Y sites. In addition, although the parent Heusler compound is cubic and exhibits weak magnetic anisotropy or no obvious magnetic anisotropy, it is found that the structure of some of these compounds is tetragonally distorted: due to this distortion, the magnetization exhibited by these compounds can be preferably aligned along the tetragonal axis. Therefore, films formed from such materials can exhibit PMA due to the magnetocrystalline anisotropy associated with their tetragonally distorted structure. Some known examples of such tetragonal Heusler compounds are Mn 3 Z, where Z = Ga, Ge, Sn and Sb, or Mn 2CoSn. So far, Si / SiO 2 The thickness of the magnetic electrodes formed from the Heusler alloy on the substrate is well over 1 nm. The thinnest layer to date is about the Heusler compound Mn 3 Ge, with layers as thin as 5 nm showing perpendicular magnetic anisotropy and reasonably square hysteresis loops. Ultrathin films (about 1 nm thick) of these materials showing large PMA grown on chemical template layers (CTLs) require the use of single crystal substrates such as MgO (100) or on Si / SiO 2 MgO seed layer on substrate. Such a single crystal substrate or the use of MgO as part of the seed layer is not useful for STT-MRAM applications, where the MTJ must be deposited on wires formed in today's CMOS-based technology from polycrystalline copper, which can be covered with other layers, which are also polycrystalline or amorphous. In order to be able to use ultrathin tetragonal Heusler compounds as magnetic electrodes switchable by STT for MRAM, methods for forming these compounds on amorphous or polycrystalline substrates are needed. Summary of the invention

[0006] A device is disclosed. The device includes a first magnetic layer and a tunnel barrier. The first magnetic layer has a volume uniaxial magnetic crystalline anisotropy. The magnetic moment of the first layer is substantially perpendicular to the first layer. The tunnel barrier is adjacent to or close to the first magnetic layer. The orientation of the magnetic moment of the first magnetic layer is reversed by a spin transfer torque caused by a current flowing between and through the first magnetic layer and the tunnel barrier. BRIEF DESCRIPTION OF THE DRAWINGS

[0007] Figure 1 . The concentrations of different N in the sputtering gas were determined by Rutherford backscattering (RBS). 2 Mn:N ratio of Mn-nitride films grown under 370 Å content.

[0008] Figure 2 . The Mn grown at different temperatures 4 RMS roughness r of N film rms .

[0009] Figure 3 . RMS roughness of MnN films as a function of Mn / N ratio rms and resistivity.

[0010] Figure 4 . Mn x Out-of-plane X-ray diffraction θ-2θ scans of N film with x=1, 2, 3, 3.76, 4 and 4.75.

[0011] Figure 5 . Depend on Figure 4 The XRD data shown in x Out-of-plane lattice constant of N film.

[0012] Figure 6 . Mn x N / Out-of-plane X-ray diffraction θ-2θ scans of CoAl layer with x=1, 2, 3, 3.76, 4 and 4.75.

[0013] Figure 7 . Deposited at room temperature Mn x N / CoAl layer Mn 3 Perpendicular magneto-optical Kerr effect (P-MOKE) hysteresis loops of Sb Heusler compounds measured as deposited and after annealing at 300°C for 30 min, where x = 1, 2, 3, 3.76, 4 and 4.75.

[0014] Figure 8 . For various thicknesses of Mn 3 Coercivity of P-MOKE hysteresis loops of Ge Heusler compounds, measured in 1 T applied field, as deposited and after sequential annealing at 300°C, 350°C and 400°C for half an hour.

[0015] Fig. 9 . Schematic diagram of a typical MTJ device stack deposited on a current-in-plane tunneling (CIPT) substrate.

[0016] Fig.10 . right Fig. 9 Hysteresis loop of a magnetometer (VSM) measured on the stack.

[0017] Fig.11 . MTJ device conductance plotted against device area. The solid line shows the linear least squares fit to the conductance data.

[0018] Fig.12 . A transmission electron microscope (TEM) image of a cross-sectional view of a representative MTJ device is shown in the left inset. The area within the black box is imaged at high resolution. The inset at the bottom right shows a magnified view of the area within the dashed box.

[0019] Fig.13 . Resistance (R) of an MTJ device with a diameter of 110 nm (nominal) versus applied field (H).

[0020] Fig.14 . Fig.12The resistance (R) versus bias voltage of the same MTJ device used in . The schematic on the right illustrates the electrical connections to the device.

[0021] Fig.15 . Measured switching probability as a function of the duration of the voltage pulse (in nanoseconds). The schematic diagram on the right illustrates the electrical connections to the device.

[0022] Fig.16 . Switching current versus duration of the voltage pulse (diagram on the left). On the right the dependence of the switching current on the inverse of the voltage pulse duration is plotted. DETAILED DESCRIPTION

[0023] Heusler compounds are formed by space group symmetry L2 1 (or D0 22 , when they are tetragonally distorted). The properties of Heusler compounds strongly depend on the chemical ordering of the elements that make up the compound. Therefore, the production of high-quality Heusler films generally requires high-temperature thermal processes: for example, deposition at temperatures significantly above room temperature and / or thermal annealing at high temperatures (above 400°C). However, such high temperatures cause interdiffusion between multiple layers within the MTJ stack, resulting in poor MTJ performance and must therefore be avoided. Recently, the inventors have disclosed highly textured, very smooth, high-quality ultrathin films of Heusler compounds that can be deposited without a thermal annealing process using a non-magnetic chemical template layer. This chemical template layer is preferably composed of a film having a B1 structure (L1 0 The chemical template layer can be deposited at room temperature and in some cases (Co-Al) chemically ordered (i.e., forming alternating atomic layers of Co and Ga or Ge or Sn or Al) even at room temperature or at significant annealing temperatures (above 400°C for Co-Ga and Co-Ge, 200-300°C for Co-Sn). The inventors have found that ultrathin films of Heusler compounds deposited on these template layers are highly epitaxial, chemically ordered, high-quality films with excellent magnetic properties, including very high values ​​of perpendicular magnetic anisotropy and square hysteresis loops (the remanent magnetic moment in zero magnetic field is close to the saturation magnetic moment). The inventors attribute this to the B1 symmetry of the template layer and the L2 symmetry of the Heusler layer. 1 or D0 22 Symmetrical similarity. The Heusler compound can be selected from Mn 3.1- x Ge、Mn 3.1-x Sn and Mn 3.1-xSb, wherein x is in the range of 0 to 1.1. Alternatively, the Heusler compound may be a ternary Heusler such as Mn 3.1-x Co 1.1-y Sn or Mn 3.1-x Co 1.1-y Sb or Mn 3.1-x Os 1.1-y Sn or Mn 3.1-x Ru 1.1-y Sn, where x≤1.2 and y≤1.0. The chemical template layer requires an insulating MgO layer as a seed layer, which limits its utility in STT-MRAM applications for switching current flow through MTJ devices. Here, the inventors show that conductive Mn x N (2.5≤x≤4) acts as a seed layer for a chemical template layer (CTL), enabling the growth of ultrathin Heusler films whose magnetic moments are switchable via STT.

[0024] Mn-nitride films are generally produced at a base pressure of about 1x10 -9 The thermally oxidized SiO with a thickness of 25 nm was deposited in an ultra-high vacuum chamber of Torr. 2 The Si substrate was sequentially cleaned in a UV ozone chamber to remove any adsorbed organic matter, rinsed in a deionized water bath to remove water-soluble contaminants and particles, exposed to hot IPA vapor to remove water, and finally dried in a hot nitrogen oven at about 60 °C. The Mn-nitride seed layer was deposited at 3 × 10 -3 The Mn-nitride layer is deposited by reactive DC magnetron sputtering in a gas mixture of Ar and nitrogen at a pressure of 100 torr from a Mn metal target. The relative ratio of Mn:N in the Mn-nitride layer can be adjusted by adjusting the N content of the sputtering gas. 2 The sputtering gas is Ar and N 2 mixture (see Figure 1 The composition of the Mn-nitride film was determined by Rutherford backscattering (RBS) by depositing it on a graphite substrate and using A series of Pt capping to prevent oxidation when exposed to the ambient environment Mn-nitride film determination. Graphite substrates containing mainly carbon (elements with atomic numbers lower than nitrogen) allow the determination of the nitrogen content of Mn-nitride films within + / - 0.5%. By varying the N content of the sputtering gas within the range of 10% to 20%, the nitrogen content of the Mn-nitride film can be determined within + / - 0.5%. 2 The content of MnN is used to obtain a MnN film having a composition of interest in the present disclosure, and the preferred composition is Mn x N, where 2.5≤x≤4. Alternatively, Mn-nitride can be grown by sputtering from a MnN target.

[0025] Film roughness is an important parameter that must be minimized to obtain high-quality MTJs with ultrathin magnetic electrodes and tunnel barriers. Therefore, a series of Mn 4 N film, and then use it Ta layer capping to prevent Mn 4 N thin film by any oxidation of environmental conditions. The film stack of these series of films is Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / in T G of Mn 4 N / Ta, where the growth temperature is T G = room temperature, 200° C., 300° C., 400° C. and 500° C. The film roughness was measured using an atomic force microscope (AFM). Figure 2 The root mean square surface roughness (r rms ). G Films deposited at ≤200°C show r rms About Therefore, after this, at T G Mn deposition at substrate temperature ≤200°C x N films, where 2.5≤x≤4. The composition dependence of the surface morphology of Mn-nitride films is Figure 3 Here, the deposition at room temperature Mn x N films, x = 1, 2, 3, 3.76, 4 and 4.75. The film stacks of these series of films are Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn x N / For a Mn:N ratio of at least 2 and not more than 4, a smooth film. This figure also summarizes the resistivity of these MnN films. The film resistivity was measured close to the center of the sample by a 4-point one-line probe technique. The spacing between the 4 contacts was about 1 mm, which is much smaller than the sample size (1" diameter). For films with an Mn:N ratio of at least 1 and not more than 2, the resistivity of the Mn-nitride film increases sharply with the Mn content or N content. At higher Mn:N ratios ≥ 3, the resistivity of the MnN film is insensitive to composition. In addition, the resistivity of the film with an Mn:N ratio of at least 2 and not more than 4 is comparable to the metal underlayers commonly used in magnetic tunnel junction stacks (e.g., the resistivity of Ti is 42 μΩ-cm and the resistivity of Ta is 95 μΩ-cm). In addition, the resistivity of the Mn-nitride film is almost one-fifth of the TaN seed layer also used in MTJ stacks (e.g., 10% N was reported to be deposited in argon by reactive RF magnetron sputtering). 2 The resistivity of the TaN film grown under the conditions of is about 700 μΩ-cm). Therefore, the Mn-nitride film is suitable for use in the MTJ stack.

[0026] X-ray diffraction (XRD) θ-2θ scans of these films were measured on a Bruker X-ray diffractometer with a GADDS area detector. These XRD measurements were performed in a symmetric out-of-plane geometry and are sensitive to film texture. Figure 4 A set of XRD scans from these films are shown, and in each case a single diffraction peak was observed. x The N film has the desired (001) orientation. The 2θ position and diffraction peak intensity are strongly dependent on the composition of the Mn-nitride film, indicating a related change in the out-of-plane lattice constant of the film, which is Figure 5 The out-of-plane lattice constant of the Mn-nitride film varies almost linearly with the Mn:N ratio. In addition, for films whose Mn:N ratio is in the range of 2.5 to 4, their out-of-plane lattice constants are similar to those of the typical tetragonal Heusler compound Mn. 3 The out-of-plane lattice constant of Sn and that of CoAl CTL are well matched. This lattice constant match promotes the growth of tetragonal Heusler compounds with the desired out-of-plane orientation. In addition, adjusting the Mn-nitride composition provides the flexibility to tune the lattice mismatch by adjusting the Mn:N ratio.

[0027] At room temperature by ion beam deposition (IBD) or by DC magnetron sputtering Mn x Grown on N films (x = 1, 2, 3, 3.76, 4 and 4.75) XRD measurements in out-of-plane geometry were performed to determine the Mn x Does the N film promote the necessary texture and alternating layer structure within the CoAl layer? The XRD data are included in Figure 6 and by having Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn x N / CoAl / Mn 3 Sb / MgO / For Mn except x=1, x For all compositions of N, in addition to the XRD peaks from the MnN layer depicted in the shaded area of ​​the figure, two peaks related to the CoAl layer are observed. These CoAl peaks correspond to the (001) and (002) reflections and demonstrate that the deposited CoAl layer has the desired (001) texture. The presence of the CoAl (001) superlattice peak clearly demonstrates the presence of alternating layers of Co and Al, which promote ordering within the Heusler compound during its growth at room temperature.

[0028] The perpendicular magneto-optical Kerr effect (P-MOKE) from this series of films was measured as a function of applied field (H). Figure 7 P-MOKE loops from samples in their as-deposited state and after annealing at 300°C for 30 min in an ultra-high vacuum furnace in a 1 T applied field are shown. x N films, no hysteresis loop is observed even after the annealing process. x N film, a P-MOKE hysteresis loop was observed after the annealing process. The P-MOKE hysteresis loop proves that the ultrathin Thick Mn 3 The SbHeusler layer is PMA. Interestingly, for Mn with x=3 and 4 x N films, even in their as-deposited state, P-MOKE hysteresis loops from ultrathin Heusler layers are observed, making them the preferred Mn-nitride compositions.

[0029] By Heusler compound (Mn 3 The coercive force (H) of Ge) was measured by P-MOKE hysteresis loop. c ) and its thermal stability to Mn 3 The dependence of Ge thickness on Figure 8 The film stack used in this study is Si / SiO 2 / Ta / Co 20 Fe 60 B 20 / Mn 3 N / CoAl / Mn 3 Ge / MgO / Ta, where t = 8, 10, 12 and The films were deposited at room temperature and P-MOKE hysteresis loops were measured in a 1 T applied field as-deposited and after sequential annealing at 300°C, 350°C and 400°C for half an hour. Mn 3 The films of the Ge layer are stable and even withstand annealing at 400°C without showing a significant change in the coercivity of the layer. SiO 2 ) have sufficient thermal stability to withstand the processing conditions commonly used during CMOS manufacturing.

[0030] Another substrate that is routinely used to evaluate the magnetic and switching properties of MTJ stacks is a CIPT substrate (CIPT stands for Current In-Plane Tunneling). These substrates have an extremely smooth surface finish (r rms About ) is coated with a thick The Si substrate is made of highly conductive W and TiN layers. Fig. 9 A schematic diagram of a typical material stack grown on a CIPT substrate (sample number G1757-37) is shown. The material stack is: CIPT substrate / Ta / Co 20 Fe 60 B 20 / Mn 3 N / CoAl / Mn 3 Ge / MgO / Co 20 Fe 60 B 20 / Ta / [ Co / Pt] 3 / Co / Ru / Co / Pt / Co / Pt] 4 / Pt / Ru. The seed layer disclosed herein Mn 3 N / CoAl promotes the growth of Heusler compounds with large PMA Mn 3 Ge. The Heusler compound is a magnetic storage electrode or a switchable magnetic layer. The tunnel barrier preferably used is MgO with a (001) texture, but other (001)-oriented tunnel barriers such as CaO and LiF can be used. Alternatively, an insulator with a spinel structure such as MgAl 2 O 4 can be used as the tunnel barrier, and its lattice spacing can be adjusted by controlling the Mg - Al composition (more preferably the Mg - Al composition Mg 1-x Al 2-x O 4 , where - 0.5 < x < 0.5), which can produce a better lattice match with the Heusler compound. For example, the reference magnetic electrode covering the tunnel barrier can include Fe, CoFe alloy, or CoFeB alloy. The magnetic moment of the reference electrode is stabilized to a high magnetic field by contacting the reference electrode with a synthetic antiferromagnet (SAF) structure (i.e., making its coercivity significantly higher than that of the switchable magnetic layer). The SAF structure used herein is Co / Pt] 3 / Co / Ru / Co / Pt / Co / Pt] 4 . It should be noted that other SAF structures not described herein can also be used instead. The capping layer can include Mo, W, Ta, Ru, Pt, or even a conductive nitride layer or a combination thereof. An optional (second) magnetic layer or a so-called "polarization enhancement layer" can be advantageously employed for even better performance (i.e., improving the tunneling magnetoresistance (TMR) or switching characteristics of the MTJ). The optional second magnetic layer can include Fe, CoFe alloy, Co 2 FeAl, Co 2 MnSi, or other Heusler compounds. The optional magnetic layer can be placed on either side or even on both sides of the tunnel barrier. A current can be induced by applying a voltage between two magnetic electrodes separated by the tunnel barrier.

[0031] Fig.10 The hysteresis loops measured for this sample after annealing it at 350°C in a high vacuum chamber for 30 minutes with a field of 1 T applied along the sample normal are shown. These vibrating sample magnetometer (VSM) measurements were performed at room temperature with the applied magnetic field oriented along the sample normal. Switching of the SAF layer was observed at fields of about 3 to 4 kOe, but Mn 3 The hysteresis loops of the GeHeusler compounds are not visible due to their low magnetic moment. The switching field of the Heusler compounds was determined to be <300 Oe by current in-plane tunneling (CIPT) measurements. These measurements were performed on a commercial instrument supplied by CAPRES A / S. The magnetic field was applied along the sample normal using a permanent magnet arranged above the sample, and the field strength was adjusted by changing the position of the magnet relative to the sample. The TMR of the sample was determined to be about 10%, and the resistance-area product (RA) was about 25 Ω-(μm) 2 .

[0032] The MTJ devices shaped like nanopillars were patterned by electron beam lithography with sizes ranging from 30nm to 250nm in diameter. The MTJ stack etch was terminated after removing nominally 10% of the CoAl layer to minimize sidewall deposition. 2 A total of 256 devices exist on a single CIPT substrate of size. Fig.11 Yield plots of all patterned MTJ devices as a graph of conductance versus device diameter are shown. These electrical tests were performed on a custom probe station. 80% of the MTJ devices showed the expected conductivity of about 25 Ω-μm 2 RA values. In addition, the MTJ device conductance varies linearly with device diameter in this logarithmic plot. The solid line is a linear least squares fit to these data and has a slope of 1.07, which is close to the expected value of 1. Switching of the magnetic state by both field and current was detected for several working devices.

[0033] Fig.12 is a transmission electron microscope image of an STT switchable MRAM device (device number 614) from another sample (sample G1746-39) containing a Heusler storage layer. This material stack is slightly different from the material stack described in detail above, being: CIPT substrate / Ta / Co 20 Fe 60 B 20 / Mn 3 N / CoAl / Mn3 Ge / MgO / Co 20 Fe 60 B 20 / Ta / [ Co / Pt] 2 / Co / Ru / Co / Pt / [ Co / Pt] 4 / Pt / Ru. Prior to electron beam lithographic patterning into nanopillar MTJ devices, the deposited material stack was annealed at 350°C in an ultrahigh vacuum chamber for 30 minutes with a field of 1 T applied along the sample normal. The diameter of the MTJ device was measured to be 102 nm, in excellent agreement with its nominal diameter of 100 nm. The slight undercut in the shape of the device results from the sidewall removal step. The high-resolution image shows multiple layers comprising the deposited material stack. The CoAl layer has a bcc texture with a (001) orientation along the sample normal. In addition, a magnified view of the area within the dashed box shows that the Mn 3 The Ge layer is very similar to the structure of the underlying CoAl layer and is grown with its tetragonal axes along the sample normal.

[0034] Fig.13 The resistance (R) versus applied field (H) loop measured by a 110 nm diameter (nominal) device is shown with the field applied in a direction perpendicular to the substrate (Device No. 501 and Sample No. G1757-37). 传感 ) The RH loop is measured in constant current mode. The switching between the low resistance state and the high resistance state is due to the rotation of the magnetic moment of the Heusler layer caused by the application of an external magnetic field (see Fig.13 ). The Heusler layer switches sharply, while the SAF structure switches much more gently (see data at fields < -2 kOe). The TMR of the device is 9.6%, consistent with CIPT measurements on blank films. Fig.14 shows the bias voltage (V 偏置 ) pulse (RV loop). The schematic on the right shows a pulse generator in series with the device to generate V 偏置 pulse. For the opposite V 偏置The polarity of the current is opposite. The resistance of the device is above the threshold V 偏置 , and the resistance of the two states (see Fig.14 The two illustrations in the figure are similar to the two states of resistance in the RH loop ( Fig.13 ). This indicates that the magnetization of the Heusler layer switches between the same two states during STT switching as observed during magnetic field-induced switching. STT switching of the Heusler layer was also independently confirmed by determining the switching phase diagram, in which it was found that the threshold switching voltage for switching between high-to-low and low-to-high resistance states (i.e. parallel-to-antiparallel and antiparallel-to-parallel magnetization states) strongly depends on the external applied magnetic field. Due to the lower integration time used in these measurements, the RV loop ( Fig.14 ) in the point-to-point noise ratio RH loop ( Fig.13 ) is high. The current density J required for STT switching of the device using a 1 ms voltage pulse c About 6×10 5 Acm -2 The J c An order of magnitude lower than similar size devices with CoFeB switchable magnetic storage electrodes. c This is ideal as MTJ devices scale to sub-20nm lithography nodes.

[0035] Fig.15 The switching probability of an MTJ device with a device diameter of 100 nm (nominal) was measured as a function of a nanosecond voltage pulse (Device No. 602, Sample No. G1757-37). A schematic diagram of the measurement setup used is shown on the right. The device is first set to its low or high resistance state (parallel or antiparallel magnetization state) by passing a 1 ms reset pulse through the MTJ device. Next, a switching voltage pulse (V p ) through the device. A total of 100 pulses were used, and the switching probability of the MTJ device resistance was determined by reading the device resistance after each pulse. (50%) At any given V p For a pulse width of 50% switching probability, it is p Increase.

[0036] Fig.16 Summarizes the relative pulse width (t p ) of the switching current (I c ) data. These data fall into two ranges, namely, precession (for t p < about 100ns) and thermally activated (t p> about 1 ms), see the figure on the left. The dashed line shows the fit of the macroscopic spin model (see D. Bedau et al., Appl. Phys. Lett. 97, 262502 (2010)). t p The inverse of (for t p < about 100ns) with I c linear change, indicating conservation of angular momentum (see Fig.16 right).

[0037] Certain structures described herein can also be used in racetrack memory devices. In this case, the racetrack is a nanowire that can include a substrate, an optional seed layer, a Mn x N / CoAl layer (where 2.5≤x≤4) and a first magnetic layer of Heusler compound. (For possible compositions of these layers, see above for Fig. 9 Note that in a racetrack memory device, there will typically be no Fig. 9 The tunnel barrier and reference or fixed magnetic layer shown in FIG. Magnetic domain walls can be moved along this racetrack, as described in U.S. Patent 6,834,005. Data can be read from (and stored in) the racetrack by interrogating (or changing) the orientation of the magnetic moment of the magnetic material between adjacent domain walls in the racetrack.

[0038] The various layers described herein may be deposited by any one or more of a variety of methods, including magnetron sputtering, electrodeposition, ion beam sputtering, atomic layer deposition, chemical vapor deposition, and thermal evaporation.

[0039] Without departing from the spirit or essential features of the present invention, the present invention may be implemented in other specific forms. The described embodiments should be considered to be illustrative in all respects only and not restrictive. Therefore, the scope of the present invention is determined by the appended claims rather than the foregoing description. All changes in the equivalent meaning and scope of the claims are encompassed within the scope.

Claims

1. A magnetic device, comprising: Mn x N layers, where 2.5≤x≤4; Covering the Mn x A template layer of an N layer, wherein the template layer comprises at least one of Co-Ga, Co-Ge, Co-Sn and Co-Al; a first magnetic layer in contact with the template layer, the first magnetic layer having volume uniaxial magnetic crystalline anisotropy, wherein a magnetic moment of the first magnetic layer is perpendicular to the first magnetic layer; and a tunnel barrier adjacent to or proximate to the first magnetic layer, wherein the orientation of the magnetic moment of the first magnetic layer is reversed by a spin transfer torque induced by a current flowing between and through the first magnetic layer and the tunnel barrier, The first magnetic layer is a ternary tetragonal Heusler compound, and the Heusler compound includes at least one of Mn2CoSn, Mn2CoSb, Mn2OsSn and Mn2RuSn.

2. The magnetic device of claim 1, wherein the ternary Heusler compound comprises Mn2CoSn.

3. The magnetic device of claim 1, comprising a second magnetic layer adjacent to or proximate to the tunnel barrier. The magnetic device of claim 3 , wherein the tunnel barrier is MgO.

5. The magnetic device of claim 3, wherein the tunnel barrier is an insulator that is lattice-matched to the first magnetic layer and allows spin filtering, the tunnel barrier comprising Mg 1-x Al 2-x O4, of which -0.5 <x<0.5。 6. A method for preparing a non-volatile memory cell, the method comprising: Using a magnetic device as a non-volatile memory cell, The magnetic device comprises: Mn x N layers, where 2.5≤x≤4; Covering the Mn x A template layer of an N layer, wherein the template layer comprises at least one of Co-Ga, Co-Ge, Co-Sn and Co-Al; a first magnetic layer in contact with the template layer, the first magnetic layer having volume uniaxial magnetic crystalline anisotropy, wherein a magnetic moment of the first magnetic layer is perpendicular to the first magnetic layer; a tunnel barrier adjacent to or proximate to the first magnetic layer, wherein the orientation of the magnetic moment of the first magnetic layer is reversed by a spin transfer torque induced by a current flowing between and through the first magnetic layer and the tunnel barrier; and a second magnetic layer adjacent to the tunnel barrier, The first magnetic layer is a ternary tetragonal Heusler compound, and the Heusler compound includes at least one of Mn2CoSn, Mn2CoSb, Mn2OsSn and Mn2RuSn.

7. The method of claim 6, comprising: The orientation of the magnetization of the first magnetic layer is switched by passing a current through the device across the tunnel barrier.

8. A magnetic device, comprising: substrate; Mn covering the substrate x N layers, where 2≤x≤4.75; A multilayer structure that is nonmagnetic at room temperature, the multilayer structure comprising alternating layers of Co and E, wherein E comprises at least one element, the at least one element comprising Al, wherein the composition of the multilayer structure is Co 1-x E x It means that x is in the range of 0.45 to 0.55, and the multilayer structure covers the Mn x N layers; a first magnetic layer comprising a Heusler compound, the first magnetic layer being in contact with the multilayer structure, wherein the first magnetic layer has a magnetic moment perpendicular to the first magnetic layer and switchable by a spin transfer torque, wherein the Heusler compound comprises at least one of Mn2CoSn, Mn2CoSb, Mn2OsSn, and Mn2RuSn; a tunnel barrier covering the first magnetic layer; and A second magnetic layer is in contact with the tunnel barrier.

9. The magnetic device of claim 8, comprising a capping layer in contact with the second magnetic layer.

10. A magnetic device, comprising: substrate; Mn covering the substrate x N layers, where 2≤x≤4.75; A multilayer structure that is nonmagnetic at room temperature, the multilayer structure comprising alternating layers of Co and E, wherein E comprises at least one element, the at least one element comprising at least one of Ga, Ge and Sn, wherein the composition of the multilayer structure is Co 1-x E x It means that x is in the range of 0.45 to 0.55, and the multilayer structure covers the Mn x N layers; a first magnetic layer comprising a Heusler compound, the first magnetic layer being in contact with the multilayer structure, wherein the first magnetic layer has a magnetic moment perpendicular to the first magnetic layer and switchable by spin transfer torque; a tunnel barrier covering the first magnetic layer; and A second magnetic layer is in contact with the tunnel barrier.

Citation Information

Patent Citations

  • Shiftable magnetic shift register and method of using the same

    US6834005B1

  • MgO tunnel barriers and method of formation

    US8008097B2

  • Magnetic device including Hessler compounds and method for providing the magnetic device

    CN110350082A

  • Templating Layers For Perpendicularly Magnetized Heusler Films

    US20180205008A1